Promosi Implementasi Kebijakan Pelayanan Prima dan KaitannyaTerhadap Kepuasan Pasien di Puskesmas Sumbul Kabupaten Dairi Tahun 2018 - Elmina Tampubolon; Diana Sinulingga; Maximilianus Dasril Samura (INSTITUT KESEHATAN DELI HUSADA, 2021)
Health is one of the elements in the general welfare that must be realized. Improving health requires information about health that can be obtained from health promotion with the Decree of the Minister of Health of the Republic of Indonesia Number 585/MENKES/SK/V/2007 concerning Guidelines for the Implementation of Health Promotion in Health Centers. In an implementation of health promotion policies inside the puskesmas and outside the puskesmas, it is to provide knowledge in the health sector in their working area and increase the satisfaction of patients visiting the puskesmas in order to improve excellent service at the puskesmas. Health promotion carried out at the Puskesmas is a strategy of empowerment, atmosphere building and advocacy which is supported by the existence of promotional media to be able to increase the satisfaction of patients who visit the Puskesmas to improve excellent health services at the Sumbul Health Center, Dairi Regency. Excellent service itself is a form of service that meets quality standards. The quality standard in question is a service that is in accordance with customer/community expectations and satisfaction. From the implementation of health promotion at the Sumbul Public Health Center, Dairi Regency, to improve excellent health services requires the involvement of special health promotion officers who receive training for health promotion and media supporting the results of puskesmas officers. Even so, there are also obstacles in the implementation of health promotion, such as community empowerment which is still not optimal as seen from the officer's information regarding areas where there are no health cadres to make it easier to provide information to the public.